STRATEGI GURU AKIDAH AKHLAK DALAM MENUMBUHKAN KARAKTER RELIGIUS SISWA - Lutfiati, Lutfiati (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2024)
This article discusses the importance of education in shaping religious character in Madrasah Tsanawiyah. Education is considered as one of the main pillars in shaping the character of the nation, because the education applied in this country has a great influence on the whole society. Religious character building means creating an environment dominated by religious values, particularly Islamic teachings and values. This environment creates an atmosphere in which a view of life that follows Islamic teachings can develop and be reflected in the attitudes and life skills of members of the madrasah community. This research uses a qualitative approach with descriptive research type. Data were collected through observation, interviews, and documentation. The research subjects were 122 students of class IX and 2 teachers of moral creed of MTs Al-Ihsan Tanah Grogot. The results showed that the formation of religious character at MTs Al-Ihsan Tanah Grogot was carried out through various efforts, including: 1) Habituation, the habituation method has proven to be very effective in instilling religious values to students. This is done by familiarizing students to perform various acts of worship, such as praying, reciting the Koran, and reading the Qur'an. 2) Exemplary, Madrasah teachers and staff become role models for students in behaving and speaking in accordance with religious values. 3) Religious activities, Madrasah organizes various religious activities, such as recitation, dhikr, and tadarus Al-Qur'an.